Behaviors and Associated Factors of Selection for Self-medication with Non-Prescription Medicines among People in Ongkharak District, Nakhon Nayok Province: Using Paracetamol, Salol et Menthol Mixture, and Oral Rehydration Salts - Phueanpinit, Pacharaporn; Tantasawat, Montira; Chaiyasothi, Thanaputt; Klanbut, Siranan (Srinagarind Medical Journal, 2022)
Background and objective: Self-medication in the general population for the management of health problems is becoming more widely accessible. This research was to investigate people's behaviors and factors associated with the risk of self-medication, which focused on 3 medication items, i.e. paracetamol, salol et menthol mixture, and oral rehydration salts (ORS). Method: The cross-sectional study was conducted by using a self-administered questionnaire, which collected data from 480 subjects of the general population in Ongkharak District, Nakhon Nayok province. Results: The majority of participants used self-medication at least 1-2 times/month (65.6%). Pharmacy was the main source for medication (95.6%), and more than half of all (65.4%) used information sources to aid in decision-making. At about 31.5% of paracetamol user groups demonstrated risk behaviors for paracetamol overdose. Overdose risk was 1.7–4.2 times higher for those with comorbidity, high income, and private sector employment. 75.1% of participants who used salol et menthol mixture were at risk for using it improperly. All occupations, with the exception of students, had a 2.1–4.4-fold higher risk of wrong indication. Approximately 75.5% of participants who used oral rehydration powder had the chance to use it improperly. Self-employed, business owners, and families with children had a 2.1–2.8-fold higher risk of selecting incorrect indications. Conclusion: The participants had access to various sources of medications and medicine information to support their decision-making. Some participants were at risk of self-medication practices that included drug overdose and inappropriate indication. The risk of self-medication was linked to factors such as income, occupation, comorbidity, and having children in the family.